Analysis of SCWB Ratio on Collapse Probability of SRPMK Concrete Structures (International Journal of Architecture and Urbanism, 2024)
The Bank Indonesia Medan Office, built in 1907, is an example of an old building requiring seismic resilience evaluation. This article investigates the impact of the Strong Column-Weak Beam (SCWB) ratio on the collapse probability of SRPMK concrete structures using spectrum response and linear time history analyses. Ground motions from Niigata (Mw 6.63), Tohoku (Mw 9.12), and Miyagi (Mw 7.15) earthquakes were utilized. Findings indicate that the existing structure does not meet seismic resilience standards per SNI 1726:2019 and SNI 2847:2019. Structural modifications are necessary with an SCWB ratio of 1.2 to ensure adequate seismic resistance. The analysis reveals that the largest inter storey drift and displacement occur during the Niigata earthquake, while the maximum base shear is recorded in spectrum response analysis. Performance evaluation of the structure shows that the collapse probability remains within the Immediate Occupancy (IO) level. This article underscores the critical role of the SCWB ratio in determining collapse probability and provides recommendations for structural design improvements.